ANALISIS PENGARUH SHARI COMPLIANCE DAN ISLAMIC CORPORATE GOVERNANCE TERHADAP JUMLAH FRAUD BANK UMUM SYARIAH PERIODE 2015—2019 - Salma Sabila; Puspita Puspita (PARADIGMA : JURNAL ILMU PENGETAHUAN AGAMA, DAN BUDAYA, 2022)
Fraud is a deviant act carried out by individuals for their own benefit but harming others. Fraud cases are still found to occur in Islamic commercial banks that run their operations based on Islamic principles. So this study aims to examine the effect of sharia compliance and Islamic corporate governance on the number of frauds in Islamic commercial banks. The independent variables used are Profit sharing ratio, Islamic income ratio, Directors-employees welfare ratio, and Islamic corporate governance. While the dependent variable used is sharia bank fraud. The research population is all Islamic commercial banks registered with the Financial Services Authority for the period 2015-2019, with a purposive sampling technique the sample used is 10 Islamic commercial banks with a study period of 5 years. The analytical method used in this research is panel data regression which is processed using Eviews 9 software. The results show that simultaneously sharia compliance and Islamic corporate governance have a significant effect on sharia commercial bank fraud. Partially, the Directors-employees welfare ratio and Islamic corporate governance have a significant positive effect on Islamic commercial bank fraud, while Profit sharing ratio and Islamic income ratio have no effect on Islamic commercial bank fraud. The results of this research have implications for practitioners and regulators in determining policies to minimize fraud.